Współczesna kryminalistyka w warunkach wojny i globalnych wyzwań XXI wieku: dzisiejsze problemy i perspektywy rozwoju - Shevchuk, Viktor (Problemy Współczesnej Kryminalistyki, 2023)
The article is devoted to the study of topical problems of criminalistic science in modern conditions of martial law and global threats of the ХХІ century. The main trends in the formation and development of criminalistics in today’s realities are identified and analyzed, and promising areas of its scientific research are outlined. The emergence and formation of new areas of criminalistic science due to scientific and technological progress, the introduction of new technologies, and the need to identify specific traces and collect evidence (genomic, digital, nuclear, etc.) are substantiated. It is noted that it is important to take into account the current trends in the development of criminalistic science associated with the formation of individual branches (directions): medical, genotyposcopy, computer (digital), aerospace and nuclear criminalistics. In the context of the war in Ukraine and large-scale aggression from the Russian Federation, the relevance of the formation of a new scientific criminalistic direction of military criminalistics is noted, and its object, subject, system and tasks are defined. The problems of the formation and development of European criminalistics and the issues of integration of criminalistics into a single European criminalistic space are analyzed. It is substantiated that further prospects for the formation and development of criminalistic science suggest the need to reboot and modernize the current paradigm. In particular, we are talking about revising and significantly updating the modern understanding of the subject of criminalistics. The expansion of the boundaries of the application of forensic knowledge, which is required not only in the investigation of crimes, and their trial in criminal proceedings but also in the use of criminalistic science in various areas of legal activity (administrative, civil, economic, arbitration proceedings and even in constitutional jurisprudence) is considered and justified. The problems of the formation and development of European criminalistics and the integration of forensic knowledge into a single European criminalistic space are analyzed.